2015
DOI: 10.3109/0886022x.2015.1065428
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 and soluble TWEAK levels are independently associated with coronary artery disease severity in patients with chronic kidney disease

Abstract: Our findings support a relationship between sTWEAK and MCP-1 levels and CAD in CKD stages 2-3 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Senescence‐associated secretory phenotype can promote secondary senescence in healthy cells (Coppe, Desprez, Krtolica & Campisi, ), and senescent cells have been demonstrated to promote aging and age‐related disease (Baker et al., , ; Zhu et al., ). Circulating levels of MCP‐1 are increased in patients with renal disease (Akdogan et al., ), cognitive impairment and Alzheimer's disease (Bettcher et al., ), atherosclerosis and cardiovascular disease (Deo et al., ). Monocyte chemoattractant protein‐1 is considered to be a marker of “inflammaging,” defined as chronic sterile inflammation that is associated with numerous age‐related diseases (Franceschi & Campisi, ).…”
Section: Resultsmentioning
confidence: 99%
“…Senescence‐associated secretory phenotype can promote secondary senescence in healthy cells (Coppe, Desprez, Krtolica & Campisi, ), and senescent cells have been demonstrated to promote aging and age‐related disease (Baker et al., , ; Zhu et al., ). Circulating levels of MCP‐1 are increased in patients with renal disease (Akdogan et al., ), cognitive impairment and Alzheimer's disease (Bettcher et al., ), atherosclerosis and cardiovascular disease (Deo et al., ). Monocyte chemoattractant protein‐1 is considered to be a marker of “inflammaging,” defined as chronic sterile inflammation that is associated with numerous age‐related diseases (Franceschi & Campisi, ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] Abnormal expression of MCP-1 has been observed in various diseases, such as clear-cell renal cell carcinoma, cerebral ischemic stroke, coronary artery disease. [ 7 9 ] Hyperglycemia can enhance the production of MCP-1 in vascular endothelial cells and its abnormal expression may contribute to the complications related to angiogenesis and vascular functions among T2DM patients. [ 6 ] Recently, growing studies have indicated that the polymorphisms of MCP-1 –2518A/G may influence the production of MCP-1 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the levels of MCP-1 in blood are related with the severity of coronary artery disease in patients with chronic kidney disease [ 20 ] and with the disease activity of rheumatoid arthritis [ 21 ]. MCP-1 is known as a prognostic factor for lung, cervical, and ovarian cancers [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%